Clinicopathological pattern and risk factors of carcinoma breast in younger age group (Bangabandhu Sheikh Mujib Medical University Journal, 2016)
Worldwide, breast cancer is the most frequently diagnosed life-threatening cancer and the leading cause of cancer death among women. Approximately 7% of all breast cancers are diagnosed in women